Estudio normativo, económico y ambiental para la adopción de vehículos eléctricos de uso doméstico para Bogotá, Colombia. (2020)
This document seeks to study and make known the regulations and tax benefits that the National Government has made available to encourage the use of electric vehicles, in order to contribute to the reduction of pollutant emissions and sustainable mobility. It shows users what infrastructure is currently available for fast charging of electric vehicles in the city of Bogotá, and what slow-charging systems can be installed in homes. The future projection that has been established for the city of Bogotá with respect to fast charging stations was also studied. The economic study emphasized why costs are the greatest obstacle to the acquisition of electric vehicles, and the environmental study sought to make a comparison of emissions between electric and internal combustion vehicles.